Kecerdasan Anak Didik Yang Mempengaruhi Perkembangan Holistik Individu - Nurrohmah, Anyi; Maslinawati, Maslinawati; Aprilia, Lala; Yulistia, Yulistia; Hadiyana Ahmad, Laila; Elnawati, Elnawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
Students' intelligence is a critical aspect in the context of modern education that affects the holistic development of individuals. This paper explores the different dimensions of student intelligence by integrating Islamic perspectives and modern theories, such as the Multiple Intelligences theory by Howard Gardner. The discussion began by defining intelligence as the ability to understand and solve problems, as well as analyzing the types of recognized intelligence, including linguistic, logical-mathematical, visual-spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalist. Factors that affect the development of students' intelligence, such as family environment, formal education, social experience, and religious values, are also discussed in depth. The approach in this paper includes an emphasis on how Islam views intelligence as a gift that must be managed wisely and used for the good of individuals as well as society. Strategies to develop students' intelligence, which include the recognition and strengthening of various types of intelligence and the application of Islamic values in education, are also considered as part of efforts to form strong character and good morals in students.